Metabolic Alterations of the Zebrafish Brain after Acute Alcohol Treatment by 1H Nuclear Magnetic Resonance Spectroscopy - Dong-Cheol Woo; Goo-Young Kim; Hyun-Ju Kim; Eunjung Bang; Hyang-Shuk Rhim; Sang-Young Kim; Do-Wan Lee; Chi-Bong Choi; Youl-Hun Seoung; Bo-Young Choe (Journal of Spectroscopy)
The purpose of this study is to investigate the metabolic alterations associated with acute alcohol treatment in zebrafish by 1H nuclear magnetic resonance spectroscopy (NMRS). The brain metabolism of zebrafish was investigated after acute alcohol treatment (one-hour long exposure of adult fish to 0.00%, 0.25%, 0.50%, or 1.00% ethyl alcohol) with whole brain extraction. The results of this study showed that glutamate (Glu) was significantly decreased, scyllo-inositol (sIns) showed a small apparent increase only in the highest acute treatment dose group, and myoinositol (mIns) showed a significant decrease. [Glu]/[tCr] and [mIns]/[tCr] levels were significantly reduced regardless of the alcohol dose, and [sIns]/[tCr] was increased in the highest alcohol treatment dose group. The present NMR study revealed that specific metabolites, such as Glu and mIns, were substantially decreased in case of acute alcohol exposed zebrafish brain.